Patients With Nonalcoholic Steatohepatitis Experience Severe Impairment of Health-Related Quality of Life. (October 2019) - Younossi, Zobair M.; Stepanova, Maria; Lawitz, Eric J.; Reddy, K. Rajender; Wai-Sun Wong, Vincent; Mangia, Alessandra; Muir, Andrew J.; Jacobson, Ira; Djedjos, C. Stephen; Gaggar, Anuj; Myers, Robert P.; Younossi, Issah; et al.
Abstract : INTRODUCTION: Although there is substantial evidence suggesting poor health-related quality of life (HRQL) in patients with chronic hepatitis C (CHC), similar data in nonalcoholic steatohepatitis (NASH) have not been fully assessed. The aim is to compare HRQL scores in patients with CHC to those with NASH. METHODS: Matched patients with advanced fibrosis (bridging fibrosis and compensated cirrhosis) due to CHC and NASH completed Short Form-36 (SF-36) questionnaire, Chronic Liver Disease Questionnaire (CLDQ), and Work Productivity and Activity Instrument questionnaire. RESULTS: We included 1, 338 patients with NASH with advanced fibrosis (mean age 57.2 years, 47% men, 55% cirrhosis) and 1, 338 matched patients with CHC. Patients with CHC and NASH had similar rates of employment and psychiatric disorders ( P > 0.05). As expected, patients with NASH had higher body mass index (mean 33.7 vs 27.6) and more type 2 diabetes (74% vs 16%) (all P < 0.01). Patients with NASH had significantly lower HRQL scores related to physical health: Physical Functioning, Bodily Pain, General Health, Vitality, Physical Summary of SF-36, and Fatigue of CLDQ ( P < 0.02). By contrast, patients with CHC had a lower Mental Health score of SF-36 and Emotional score of CLDQ and reported greater impairment in daily activities as measured by the Work Productivity and Activity Instrument questionnaire ( P < 0.002). In multivariate analysis, after adjustment for demographic parameters, cirrhosis, and history of psychiatric disorders, having NASH was associated with lower physical HRQL scores and higher mental health–related scores ( P < 0.05). DISCUSSION: Patients with NASH and advanced fibrosis have more impairment of their physical health–related scores than patients with CHC with advanced fibrosis. These data should dispel the misconception that NASH is an asymptomatic disease with little negative impact on patients' well-being.